Intramural hematoma in the proximal sealing zone of the thoracic endovascular aneurysm repair: frequency and safety in acute and subacute type B dissections - Lescan, Mario; Mustafi, Migdat; Hahn, Julia; Schlensak, Christian; Andic, Mateja (Frontiers in Cardiovascular Medicine, 2023)
Introduction To assess the outcomes after thoracic endovascular aneurysm repair (TEVAR) in the presence of intramural hematoma (IMH) in the proximal sealing zone. Material and methods Patient data were retrospectively extracted from the hospital records of patients treated with TEVAR for acute and chronic aortic dissection type B in one single center. The initial, preoperative, first postoperative, and last follow-up CT scans were evaluated in the aortic 3D multiplanar reformats and the centerline regarding IMH presence in the proximal sealing zone, anatomical preconditions, and the morphological TEVAR complications including migration and bird-beak. Groups with (IMH) and without IMH (no-IMH) were compared. Results Overall, 84 patients (IMH:42; no-IMH:42) were treated at the age of 63(55; 72) years, of whom 23/84 (27%), 34/84 (40%), and 27/84 (32%) were in the hyperacute, acute and subacute dissection phases, respectively. The bovine arch was found in 10/84(12%) and the type III arch was most common (43/84;51%). IMH maximum extent was found in zones 0, 1, 2, and 3 in 14/84 (17%), 17/84 (20%), 18/84 (21%), and 6/84 (7%), respectively. Sealing was achieved in zone II in 71/84 (85%) and LSA was revascularized in 66/84 (79%) of the overall cohort. Early mortality and paraplegia were 2/84 (2%) each; stroke rate was 3/84 (4%). During the 22 months median follow-up (22;4;43) no RTAD was observed. Migration ≥10mm (IMH: 11/82; no-IMH: 10/82; P=1.0) and bird-beaks (IMH: 10/82; no-IMH: 12/82; P=0.8036) were comparable in both groups and accompanied by a low aorta related mortality (1/82) in both groups. Conclusion The presence of the IMH in the proximal TEVAR sealing zone is frequent and may not be relevant for the occurrence of the RTAD, stent-graft migration, or bird-beak formation.